Nanometer-scale dynamics of high-temperature levitated liquids - Price, D.L.; Hennet, L.; Pozdnyakova, I.; Saboungi, M.-L. (Condensed Matter Physics, 2008)
We review recent measurements of the microscopic dynamics of high-temperature liquids made with inelastic
x-ray scattering and aerodynamic levitation of the samples. Phenomenological and theoretical interpretations
are also discussed. Ми робимо огляд недавнiх дослiджень мiкроскопiчної динамiки високотемпературних рiдин, зроблених з непружнiм розсiянням рентгенiвських променiв та аеродинамiчною левiтацiєю зразкiв. Обговорюються також феноменологiчнi та теоретичнi iнтепретацiї.